Kebijakan Dividen: Struktur Kepemilikan, Kebijakan Utang, Kesempatan Investasi, dan Profitabilitas - Muhammad Ihsan Budi Santoso; Kusumawati, Eny (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Dividend policy is a decision whether the profit earned by the company will be distributed to shareholders as dividends or will be retained in the form of retained earnings for future investment financing. This study aims to analyze the effect of ownership structure, debt policy, investment opportunities, and profitability on dividend policy in non-financial companies on the IDX for the 2021-2023 period. The sampling technique used in this study was purposive sampling. A total of 258 companies have met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results provide empirical evidence that debt policy affects dividend policy, the looser the debt policy (high DER ratio), the percentage of dividends distributed will decrease. Profitability affects dividend policy, the higher the profitability ratio in the company, the percentage of dividends distributed will increase. Meanwhile, ownership structure and investment opportunities have no effect on dividend policy. These findings provide important empirical and practical contributions to stakeholders, especially companies and investors, regarding factors that have contributed to dividend policy in non-financial companies listed on the Indonesia Stock Exchange (IDX).